Tactical considerations in the middle-distance running events at the 2012 Olympic Games: a case study - Renfree, A.; Mytton, G. J.; Skorski, S.; St Clair Gibson, A. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To identify tactical factors associated with progression from preliminary rounds in middle-distance running events at an international championship. Methods: Results from the 2012 Olympic Games were used to access final and intermediate positions, finishing times, and season-best (SB) times for competitors in men`s and women`s 800-m and 1500-m events (fifteen 800-m races and ten 1500-m races). Finishing times were calculated as %SB, and Pearson product-moment correlations were used to assess relationships between intermediate and finishing positions. Probability (P) of qualification to the next round was calculated for athletes in each available intermediate position. Results: There were no significant differences in finishing times relative to SB between qualifiers and nonqualifiers. In the 800-m, correlation coefficients between intermediate and final positions were r = .61 and r = .84 at 400 m and 600 m, respectively, whereas in the 1500-m, correlations were r = .35, r = .43, r = .55, and r = .71 at 400 m, 800 m, 1000 m, and 1200 m, respectively. In both events, probability of qualification decreased with position at all intermediate distances. At all points, those already in qualifying positions were more likely to qualify for the next round. Conclusions: The data demonstrate that tactical positioning at intermediate points in qualifying rounds of middle-distance races is a strong determinant of qualification. In 800-m races it is important to be in a qualifying position by 400 m. In the 1500-m event, although more changes in position are apparent, position at intermediate distances is still strongly related to successful qualification.